Rhodotorula fungemia in a patient with acute lymphoblastic leukemia - Mehmet Erinmez; Yasemin Zer; Ayşe Büyüktaş Manay (Universidade de Santa Cruz do Sul, 2022)
Objectives: Rhodotorula is an environmental yeast that belongs to Basidiomycota Phylum. Rhodotorula species are ubiquitous in nature, can be found in soil and freshwater. Immunocompromised patients can develop Rhodotorulosis due to wide-ranging exposure to Rhodotorula in the hospital environment. Case Discussion: The patient was a 3-year-old male with a diagnosis of Pro B-Acute Lymphoblastic Leukemia (ALL). He was admitted to the hospital with complaints of malaise, fatigue, weight loss, and diarrhea between courses of chemotherapy. Rhodotorula was isolated from the patient's blood culture obtained during the elevation of temperature. After 14 days of amphotericin B treatment, clinical situation of the patient was improved and he was discharged. Conclusion: Rhodotorula spp. as a rare yet emerging pathogen, often presents as fever of unknown etiology resistant to antibacterial treatment and can be associated with fungemia and other severe complications.